Pharmacokinetic and pharmacodynamic studies of N-acetylcysteine, a potential chemopreventive agent during a phase I trial - Pendyala, L; Creaven, P J (Cancer epidemiology, biomarkers & prevention, 1995)
A Phase I, pharmacokinetic and pharmacodynamic study of N-acetylcysteine (NAC), a potential chemopreventive agent, given daily p.o. for 6 months was carried out in 26 volunteers at higher than normal risk of malignancy. The goals of the study were to define the highest nontoxic dose, the toxicity profile, and the pharmacokinetics and pharmacodynamics of NAC. The pharmacodynamic end points studied included glutathione (GSH) in plasma, RBC and peripheral blood lymphocytes (PBL), cysteine in plasma, and two GSH-metabolizing enzymes glutathione S-transferase and oxidized glutathione reductase in PBL. The study was carried out in 2 stages. The first stage consisted of an inter- and intrasubject dose escalation; the second, an assessment of a single daily dose. Starting doses for the first 4 cohorts of 3 subjects were 400, 800, 1600, and 3200 mg/m2/day in divided doses doubled at the end of each month in the absence of toxicity to a final dose of 6400 mg/m2/day. The total planned period on NAC for each subject was 6 months. Pharmacokinetic and pharmacodynamic measurements were carried out at the beginning of the study and at the end of each month. The second stage of the study consisted of a daily dose of 800 mg/m2/day. During this part of the study, NAC in plasma and GSH and oxidized glutathione reductase (GRD) in PBL were measured on day 1 and again at the end of first, second, and sixth month on NAC. Major toxicities were bad taste and gastrointestinal disturbances. The highest nontoxic dose was 800 mg/m2/day in most of the subjects.